Synergistic effect of ursolic acid and piperine in CCl4 induced hepatotoxicity - Sayan Biswas; Amit Kar; Nanaocha Sharma; Pallab K. Haldar; Pulok K. Mukherjee (Annals of Medicine, 2021)
AbstractBackground Ursolic acid (UA) is a potent plant-based hepatoprotective agent having poor bioavailability, which hampers its therapeutic efficacy. The present study tries to overcome this limitation by combining it with piperine (PIP), a proven bioenhancer and hepatoprotective agent.Methods The type of interaction (synergism, addition, or antagonism) resulting between UA and PIP was analyzed and quantified by isobologram and combination index analysis. The hepatoprotective activity of UA and PIP was evaluated by measuring the level of hepatic marker enzymes. Pharmacokinetic analysis was carried out to ascertain the improvement of bioavailability.Results The combinations significantly decrease the enzyme levels, which indicate better hepatoprotective activity compared to single drugs. The relative oral bioavailability of UA was increased about tenfold (from AUC0–t =12.78 ± 2.59 µg/h/ml to 125.15 ± 1.84 µg/h/ml) along with the improvement of plasma concentration and elimination half-life.Conclusions The findings indicated that the combination of PIP and UA is an effective strategy in enhancing the bioavailability and hepatoprotective potential of UA.KEY MESSAGESUrsolic acid in a combination with piperine provides a synergistic hepatoprotective effect in carbon tetrachloride induced liver damage in rats.Piperine improves the pharmacokinetic properties of ursolic acid when given in combination.Piperine improves the relative oral bioavailability of ursolic acid by tenfold when combined together.